Build a Sustainable Vaccines Industry with Synthetic Biology. Issue 9 (September 2021) - Kitney, Richard I.; Bell, Jennifer; Philp, Jim
Abstract : The vaccines industry has not changed appreciably in decades regarding technology, and has struggled to remain viable, with large companies withdrawing from production. Meanwhile, there has been no let-up in outbreaks of viral disease, at a time when the biopharmaceuticals industry is discussing downsizing. The distributed manufacturing model aligns well with this, and the advent of synthetic biology promises much in terms of vaccine design. Biofoundries separate design from manufacturing, a hallmark of modern engineering. Once designed in a biofoundry, digital code can be transferred to a small-scale manufacturing facility close to the point of care, rather than physically transferring cold-chain-dependent vaccine. Thus, biofoundries and distributed manufacturing have the potential to open up a new era of biomanufacturing, one based on digital biology and information systems. This seems a better model for tackling future outbreaks and pandemics. Highlights: Biofoundries incorporate high levels of automation that implement complex workflows in order to increase the reliability and reproducibility of biotechnology. Biofoundries in different locations can communicate via digital data to complete design/build/test/learn operations. Distributed manufacturing attempts to bring small-scale manufacturing to many locations, directly in contradiction to the centralised mass production paradigm. Biofoundries are suited to the design of certain types of vaccines that do not require whole cells. The design and prototyping of vaccines in biofoundries with final manufacture in small-scale facilities offers the possibility to bring manufacturing close to the point of care. The marriage of biofoundries and the distributed manufacturing model offers solutions to the troubled vaccines manufacturing industry.